Perception of the labor social climate and the personal efficiency in professionals of the health of the public sector of the city of Lima - Bulnes Bedón, Mario (2004)
OBJECTIVES: To need interaction between the Perception the Labor Social Climate and the Perception of the personal efficiency in the professionals of the health. DESIGN: He is descriptive, comparative and corelational, of charater analytic in which it treated to determine the prevalence and distribution of professional wearing down in the professionals of the health. MATERIAL AND MÉTODOS: It is conformed by 93 professionals of the health of publics hospitable centers between social doctors, nurses, obstetrics, psychologists, workers and technologies doctors. For evaluation of the variables the Climate Scale elaborated by Rudolf Moos and Bernice Moos, and the Inventory of .Burnout. Were used Labor Social elaborated by Cristina Maslach and Susan Jackson.